1997
DOI: 10.1037/0278-7393.23.5.1059
|View full text |Cite
|
Sign up to set email alerts
|

Long-term semantic priming: A computational account and empirical evidence.

Abstract: Semantic priming is traditionally viewed as an effect that rapidly decays. A new view of long-term word priming in attractor neural networks is proposed. The model predicts long-term semantic priming under certain conditions. That is, the task must engage semantic-level processing to a sufficient degree. The predictions were confirmed in computer simulations and in 3 experiments. Experiment 1 showed that when target words are each preceded by multiple semantically related primes, there is long-lag priming on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
225
5
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(246 citation statements)
references
References 66 publications
(148 reference statements)
13
225
5
3
Order By: Relevance
“…We make this claim for several reasons. First, consistent with Becker et al (1997), we reject the idea that simple spreading activation can account for the persistent priming observed in the processing of new exemplars. Persistent priming of lexical or semantic memory representations seems possible only for information directly processed in the priming events.…”
Section: Theoretical Interpretation Of Altm Effectssupporting
confidence: 63%
See 2 more Smart Citations
“…We make this claim for several reasons. First, consistent with Becker et al (1997), we reject the idea that simple spreading activation can account for the persistent priming observed in the processing of new exemplars. Persistent priming of lexical or semantic memory representations seems possible only for information directly processed in the priming events.…”
Section: Theoretical Interpretation Of Altm Effectssupporting
confidence: 63%
“…Although semantic priming effects have traditionally been thought to last only a few seconds at most, there is recent evidence that such priming can be more persistent (Becker, Moscovitch, Behrmann, & Joordens, 1997;Hughes & Whittlesea, 2003;. The demonstrations of persistent semantic priming have depended on more complex priming operations and, sometimes, multiple priming events.…”
Section: Magnitude and Persistence Of The Priming Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This choice was not imposed by the mean field approach itself. Contrary to localist models were items are coded by single nodes (Anderson 1976(Anderson , 1983aCollins and Loftus 1975;Collins and Quillian 1969), the mean field approach is compatible with neurons coding for several items in memory and populations overlap, as in distributed models (Lerner et al in press, 2010;Ursino et al 2011;Cree et al 1999;Becker et al 1997;Masson 1995;Plaut 1995;Moss et al 1994). Such overlap has been the object of studies on in cortical network models and would not change qualitatively the effects observed here (Romani et al 2006;Curti et al 2004).…”
Section: Neural Coding Of Conceptsmentioning
confidence: 93%
“…So for example, participants are more accurate in identifying a quickly flashed word in a perceptual identification task if it was studied a few minutes or hours previously (e.g., Jacoby & Dallas, 1981). The longevity of this priming distinguishes it from various forms of short term priming phenomena --such as semantic or masked priming --that tend to last a few seconds (e.g., Henderson, Wallis, & Knight, 1984;Forster & Davis, 1984; but for exceptions to this general rule, see Becker, Moscovitch, Behrmann, & Joordens, 1997;.In a recent series of articles, Ratcliff and McKoon (R&M) have challenged the common view that priming reflects a facilitation in processing test stimuli, and argued instead that priming is a bias to interpret test items as previously studied materials (McKoon & Ratcliff, 1995, 1996Ratcliff, Allbritton, McKoon, 1997;Ratcliff, McKoon, 1995, 1996, Ratcliff, McKoon, Verwoerd, 1989. That is, rather than simply reflecting a benefit in processing repeated materials, priming is interpreted as a mixture of benefits for repeated and costs for related study/test items, with costs equaling benefits.…”
mentioning
confidence: 99%